Solid-liquid dual-state high-performance reusable buffering energy-absorbing structural material and processing technology
Through metal bonding and nano-scale transition layer processing of aluminum alloy and nickel-titanium shape memory alloy composite structure, combined with multi-point welding and vacuum casting technology, the bonding strength and durability of traditional materials are solved, and high performance and high durability are achieved cushioning energy absorbing material.
Patent Information
- Application Number
- CN202411221718.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional buffer energy-absorbing materials have shortcomings in structural stability and reusability. Combined with low strength, easy interface separation, stress concentration, oxidation resistance and corrosion resistance, it is difficult to meet the needs of high-performance and high-durability materials.
The composite structure of the aluminum alloy core and the nickel-titanium shape memory alloy shell is connected through metal bonding technology and nano-scale transition layer, combined with multi-point welding and vacuum casting technology, the metal lining and honeycomb structure are set up, and nano-coating treatment is applied. and heat treatment process ensures high bond strength and durability of the material.
It significantly improves the bonding strength and stability of the material, extends the service life, avoids stress concentration, enhances oxidation resistance and corrosion resistance, and ensures that good mechanical properties and energy absorption efficiency are maintained after multiple uses.
Smart Images

Figure CN119122972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of buffering energy absorbing structural materials, and in particular to a solid-liquid dual-state high-performance reusable buffering energy absorbing structural material and a processing technology. Background Art
[0002] Traditional buffering and energy-absorbing materials have significant deficiencies in structural stability and reusability. Usually, after being subjected to multiple impacts, the energy absorption performance of the material will gradually decay, and it is difficult to restore it to its original state through a simple process. In addition, the bonding strength between different metal layers of traditional materials is often low, and the overall structure is prone to failure due to interface separation, especially under high stress and high temperature conditions. Traditional processes are also difficult to control the uniformity of the microstructure, and stress concentration is prone to occur, thereby reducing the overall performance of the material. At the same time, traditional materials also perform poorly in terms of oxidation resistance and corrosion resistance, have a short service life, and are prone to performance degradation in complex environments. The above shortcomings have caused traditional buffering and energy-absorbing materials to perform poorly in high-demand application scenarios, and it is difficult to meet the needs of modern industry for high-performance and high-durability materials, and they need to be optimized and improved. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems raised in the above background technology.
[0004] The present invention adopts the following technical scheme: a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material and a processing technology, wherein the structural material comprises: a composite structure consisting of an aluminum alloy core and a nickel-titanium shape memory alloy shell, wherein the aluminum alloy core is located inside and the nickel-titanium shape memory alloy shell is coated on the outside;
[0005] The aluminum alloy core and the nickel-titanium shape memory alloy shell are tightly connected by metal bonding technology, and the connection interface is coated with a nano-scale transition layer to improve the bonding strength between different metals.
[0006] Preferably, the aluminum alloy core and the nickel-titanium shape memory alloy shell are connected by the following structure: a metal lining is arranged in the middle, the lining is sandwiched between the aluminum alloy core and the nickel-titanium shape memory alloy shell, and the lining is respectively fixed to the aluminum alloy core and the nickel-titanium shape memory alloy shell by a multi-point welding process;
[0007] The multi-spot welding process adopts pulse welding technology to control the size and distribution of welding points to ensure a stable connection between the aluminum alloy core and the nickel-titanium shape memory alloy shell. Here, by setting a metal lining between the aluminum alloy core and the nickel-titanium shape memory alloy shell and adopting a multi-spot welding process, the structure effectively improves the strength and stability of the connection. The presence of the lining buffers the difference in thermal expansion coefficient between the aluminum alloy and the nickel-titanium alloy, reduces the problem of interface stress concentration, and prolongs the service life of the material in high stress and complex environments.
[0008] Preferably, the aluminum alloy core and the nickel-titanium shape memory alloy shell are formed by the following partition connection structure: the aluminum alloy core is a honeycomb structure, which is connected to the nickel-titanium shape memory alloy shell by a matching corrugated or stepped interlocking structure;
[0009] Each honeycomb unit in the mosaic structure matches the corrugated or stepped shape of the shell through precision machining technology to achieve a high-precision tight connection. Here, a mosaic structure of a honeycomb aluminum alloy core and a corrugated or stepped nickel-titanium alloy shell is used to achieve a high-precision connection through precision machining technology. Such a partitioned connection structure improves the overall rigidity and deformation resistance of the material, ensures the integrity of the structure during multiple energy absorption processes, and further enhances the durability and adaptability of the material.
[0010] A processing technology for a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material, the preparation process of the material comprising the following steps:
[0011] Additively manufacture complex lattice structures of nickel-titanium shape memory alloys by selective laser melting (SLM) technology, the lattice structures are hollow in design to facilitate subsequent filling with aluminum alloy;
[0012] The nickel-titanium alloy lattice structure is placed in a vacuum casting mold to prepare for casting of the aluminum alloy.
[0013] Preferably, the vacuum casting process comprises the following steps:
[0014] The aluminum alloy is heated to a molten state under a vacuum environment;
[0015] The molten aluminum alloy is injected into the hollow part of the nickel-titanium alloy lattice structure through the pouring port, and a tightly bonded composite structure is formed after the aluminum alloy cools. Here, the vacuum casting process melts and casts the aluminum alloy in a vacuum environment, ensuring a tight bond between the aluminum alloy and the nickel-titanium alloy and avoiding the introduction of bubbles and impurities. This process improves the internal density and bonding strength of the material, thereby enhancing the overall structural performance and durability of the composite material.
[0016] A processing technology for a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material, another preparation process of the material comprises the following steps:
[0017] The aluminum alloy rod is pre-processed into a desired shape and filled into a nickel-titanium shape memory alloy tube;
[0018] A plurality of rod-shaped structures of aluminum alloy and nickel-titanium alloy dual materials are combined into a lattice structure material through a mechanical assembly process.
[0019] Preferably, the mechanical assembly process comprises the following steps:
[0020] Precisely align multiple aluminum alloy and nickel titanium bi-material rod structures;
[0021] The hot melt welding process is used to fix these rod-like structures together to form an overall lattice structure. Here, the hot melt welding process is used to fix the rod-like structures of aluminum alloy and nickel-titanium alloy together to ensure the integrity and strength of the lattice structure. Hot melt welding technology can effectively control the welding temperature and area, reduce the adverse effects on material properties during the welding process, and improve the stability and durability of the final structure.
[0022] Preferably, the material processing technology also includes:
[0023] Apply nano-coating treatment on the connection interface between aluminum alloy and nickel-titanium shape memory alloy to improve its oxidation resistance and corrosion resistance;
[0024] The coating is achieved through an electrochemical deposition process to ensure uniformity and adhesion of the coating. Here, nano-coating treatment is applied to the connection interface between the aluminum alloy and the nickel-titanium alloy to improve the material's oxidation resistance and corrosion resistance. The uniformity and adhesion of the coating achieved through the electrochemical deposition process ensure the long-term stability of the material in harsh environments, further extending the service life of the composite material.
[0025] Preferably, the preparation process of the material further comprises:
[0026] After the final forming, the material is subjected to a heat treatment process to stimulate the shape memory effect of the nickel-titanium shape memory alloy, and the heat treatment temperature is controlled at about 700 degrees Celsius;
[0027] By precisely controlling the heat treatment time and temperature, the nickel-titanium shape memory alloy can quickly return to its original shape after the material is deformed. Here, by subjecting the material to a heat treatment process after final forming, the shape memory effect of the nickel-titanium shape memory alloy is stimulated, so that the material can quickly return to its original shape after deformation. Precisely controlling the heat treatment time and temperature ensures the durability and reliability of the shape memory effect, so that the material can still maintain good energy absorption performance after repeated use.
[0028] Compared with the prior art, the advantages and positive effects of the present invention are:
[0029] 1. In the present invention, by adopting metal bonding technology and nano-level transition layer treatment, the bonding strength between the aluminum alloy core and the nickel-titanium shape memory alloy shell is significantly improved, avoiding the interface separation problem that may occur in traditional materials under high stress conditions. This improvement ensures the stability and durability of the overall structure, and can maintain good mechanical properties after repeated use.
[0030] 2. In the present invention, the internal structure and stress distribution of the material are precisely controlled through selective laser melting (SLM) additive manufacturing, vacuum casting, mechanical assembly and coating treatment, avoiding the stress concentration problem in traditional processes. In particular, the application of nano-coating effectively improves the oxidation resistance and corrosion resistance of the material, allowing it to maintain a long service life in complex environments and meet the needs of high-performance applications.
[0031] 3. In the present invention, the shape memory effect of nickel-titanium shape memory alloy is further enhanced by precisely controlling the time and temperature in the heat treatment process. This treatment ensures that the material has stable performance after multiple impact energy absorption and can quickly recover to its initial state after multiple deformations, thereby maintaining energy absorption efficiency and avoiding performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The structural schematic diagram of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material proposed by the present invention;
[0033] Figure 2 The present invention provides a schematic diagram of the process structure of a processing technology for a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material. DETAILED DESCRIPTION
[0034] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0036] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the technical field.
[0037] Embodiment 1
[0038] The present invention provides a technical solution: a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material, which includes a composite structure consisting of an aluminum alloy core and a nickel-titanium shape memory alloy shell. The aluminum alloy core is designed as a honeycomb structure, located inside the material, and is used to provide energy absorption. The nickel-titanium shape memory alloy shell is coated on the outside of the aluminum alloy core, and the two are tightly connected by metal bonding technology. The connection interface is coated with a nano-scale transition layer to enhance the bonding strength and durability between different metals.
[0039] Processing technology of solid-liquid dual-state high-performance reusable buffer energy-absorbing structural materials: Lattice structure manufacturing: The complex hollow lattice structure of nickel-titanium shape memory alloy is manufactured by selective laser melting (SLM) additive manufacturing technology. Vacuum casting: The nickel-titanium alloy lattice structure is placed in a vacuum casting mold, and then the aluminum alloy is heated to a molten state, and the molten aluminum alloy is injected into the hollow part of the lattice structure through a pouring port under a vacuum environment, and a tightly combined composite structure is formed after cooling. Lining welding: A metal lining is set between the aluminum alloy core and the nickel-titanium shape memory alloy shell, and the lining is fixed to the aluminum alloy core and the nickel-titanium alloy shell respectively through a multi-point welding process. Pulse welding technology is used to control the size and distribution of the welding points to ensure the stability of the structure. Nano-coating treatment: A nano-scale transition layer is applied to the connection interface between the aluminum alloy and the nickel-titanium alloy for coating, and the uniformity and adhesion of the coating are achieved through an electrochemical deposition process to enhance the oxidation resistance and corrosion resistance. Heat treatment: After the final molding, the composite material is heat treated and heated to about 700 degrees Celsius to stimulate the shape memory effect of the nickel-titanium shape memory alloy. By precisely controlling the heat treatment time and temperature, the material can quickly recover to its original shape after deformation, ensuring stable performance after repeated use.
[0040] Embodiment 2
[0041] The present invention provides a technical solution: a solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material, which is composed of an aluminum alloy rod and a nickel-titanium shape memory alloy tube. The aluminum alloy rod is the core material, located inside the structure, and is pre-processed to adapt to the external tube. The nickel-titanium shape memory alloy tube is coated on the outside of the aluminum alloy rod, and the two are mechanically assembled to form a tightly combined lattice structure. Each aluminum alloy rod is precisely matched with the inner wall of the nickel-titanium alloy tube to ensure the mechanical properties and energy absorption effect of the entire structure.
[0042] Processing technology of solid-liquid dual-state high-performance reusable buffer energy-absorbing structural materials: Matching of aluminum alloy and nickel-titanium alloy: Fill the aluminum alloy rod pre-processed into the required geometric shape into the prefabricated nickel-titanium shape memory alloy tube to ensure the close fit between the rod and the tube. Mechanical assembly: Through precision alignment technology, multiple dual-material rod-shaped structures of aluminum alloy and nickel-titanium shape memory alloy are assembled to form a lattice structure. Each unit of this structure is connected by a hot melt welding process to ensure that the assembled lattice structure has sufficient strength and stability. Nano-coating treatment: Nano-coating treatment is performed on the connection interface between aluminum alloy and nickel-titanium alloy, and a uniform coating is formed on the interface through an electrochemical deposition process to enhance the material's oxidation resistance and corrosion resistance. Heat treatment: The assembled lattice structure is heat-treated to heat the material to about 700 degrees Celsius to stimulate the shape memory effect of nickel-titanium shape memory alloy. The heat treatment process ensures the rapid recovery performance of nickel-titanium alloy after deformation by controlling temperature and time, so that the lattice structure material maintains excellent energy absorption effect during multiple uses.
[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. Solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material, characterized by: The structural material comprises: a composite structure consisting of an aluminum alloy core and a nickel-titanium shape memory alloy shell, wherein the aluminum alloy core is located inside and the nickel-titanium shape memory alloy shell is coated on the outside; The aluminum alloy core and the nickel-titanium shape memory alloy shell are tightly connected through metal bonding technology, and the connection interface is coated with a nano-scale transition layer to improve the bonding strength between different metals.
2. The solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to claim 1, characterized in that: The aluminum alloy core and the nickel-titanium shape memory alloy shell are connected by the following structure: a metal lining is provided in the middle, the lining is sandwiched between the aluminum alloy core and the nickel-titanium shape memory alloy shell, and the lining is fixed to the aluminum alloy core and the nickel-titanium shape memory alloy shell respectively by a multi-point welding process; The multi-spot welding process uses pulse welding technology to control the size and distribution of welding points to ensure a stable connection between the aluminum alloy core and the nickel-titanium shape memory alloy shell.
3. The solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to claim 1, characterized in that: The aluminum alloy core and the nickel-titanium shape memory alloy shell are connected by the following partitioned structure: the aluminum alloy core is a honeycomb structure, which is connected to the nickel-titanium shape memory alloy shell by a matching corrugated or stepped interlocking structure; Each honeycomb unit in the interlocking structure is matched with the corrugated or stepped shape of the outer shell through a precision machining process to achieve a high-precision tight connection.
4. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to any one of claims 1 to 3, characterized in that: The preparation process of the material comprises the following steps: Additively manufacture complex lattice structures of nickel-titanium shape memory alloys using selective laser melting (SLM) technology. The lattice structures are hollow and can be subsequently filled with aluminum alloy. The nickel-titanium alloy lattice structure is placed in a vacuum casting mold to prepare for casting of the aluminum alloy.
5. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to claim 4 is characterized in that: The vacuum casting process comprises the following steps: The aluminum alloy is heated to a molten state under a vacuum environment; The molten aluminum alloy is injected into the hollow part of the nickel-titanium alloy lattice structure through the pouring port, and a tightly bonded composite structure is formed after the aluminum alloy is cooled.
6. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to any one of claims 1 to 3, characterized in that: Another preparation process of the material comprises the following steps: The aluminum alloy rod is pre-processed into the desired shape and filled into the nickel-titanium shape memory alloy tube; A plurality of rod-shaped structures of aluminum alloy and nickel-titanium alloy dual materials are combined into a lattice structure material through a mechanical assembly process.
7. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to claim 6, characterized in that: The mechanical assembly process comprises the following steps: Precisely align multiple aluminum alloy and nickel titanium bimaterial rod structures; These rod-like structures are fixed together using a hot melt welding process to form an overall lattice structure.
8. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to any one of claims 4 to 7, characterized in that: The processing technology of the material also includes: Apply nano-coating treatment on the connection interface between aluminum alloy and nickel-titanium shape memory alloy to improve its oxidation resistance and corrosion resistance; The coating is achieved through an electrochemical deposition process, ensuring the uniformity and adhesion of the coating.
9. The processing technology of the solid-liquid dual-state high-performance reusable buffer energy-absorbing structural material according to any one of claims 1 to 8, characterized in that: The preparation process of the material also includes: After the final forming, the material is subjected to a heat treatment process to stimulate the shape memory effect of the nickel-titanium shape memory alloy, and the heat treatment temperature is controlled at about 700 degrees Celsius; By precisely controlling the heat treatment time and temperature, the nickel-titanium shape memory alloy can quickly recover to its original shape after deformation.
